La Sala Polivalente di Bondo, ovvero il restauro del contemporaneo - Armando Ruinelli; Anna Innocenti (ArchAlp)
Designed by Armando Ruinelli in 1995, the Multipurpose Hall in Bondo represents a rare case in which an architect, after completing a project, remains engaged with the space over time. Now, nearly three decades later, he has been entrusted with its restoration, marking a new chapter in his architectural journey. Influenced by Aldo Rossi and Michael Alder, Ruinelli developed a design methodology rooted in typological analysis, material selection, and a sensitive response to the built environment. The Multipurpose Hall, situated in a landscape rather than an urban setting, showcases his evolving understanding of architecture’s relationship with nature. Constructed as a simple composition of a concrete base and a wooden structure, the building harmonises with its surroundings through subtle yet precise design choices. In 2017, a devastating landslide severely damaged the structure. The current restoration, to be completed by the end of this year, focuses on three key aspects: repair, correction, and adaptation. Functional updates include new flooring, enhanced glazing, and upgraded infrastructure, while aesthetic refinements address prior material choices and architectural details. The intervention also responds to the transformed landscape, integrating the building into a newly designed environment that merges protective infrastructure with historical rural elements.